Evaluation of management practices against bollworms in cotton - SUMAN DEVI; PALA RAM; KRISHNA ROLANIA; AJAY KUMAR (The Indian Journal of Agricultural Sciences, 2021)
A field experiment was conducted at Entomology Research Area, CCS Haryana Agricultural University, Hisar to evaluate the management practices, viz. use of botanical pesticides, Trichogramma chilonis (Hymenoptera: Trichogrammatidae) release and intercropping with sesame were evaluated alone and in different combination against spotted bollworm, Earias spp. (Lepidoptera: Noctuidae) and pink bollworm, Pectinophora gossypiella Saunders (Lepidoptera: Gelechiidae) in cotton during 2016-17. From investigation, it was concluded that all practices, either alone or in combinations, provided significantly better control of spotted bollworm and pink bollworm than the control. The results revealed that lowest incidence of spotted bollworm (10.09 and 8.10%) recorded in treatment T2 (Spinosad 45 SC @ 75 ml/acre) which was found at par with the treatment T3 (Spinosad 45 SC @ 75 ml/ acre alternated with nimbecidine) i.e. 10.13 and 9.14%, and T6 (Intercropping cotton with sesame + Release of T. chilonis adults alternated with nimbecidine) i.e. 10.14 and 8.41% during 2016-17, respectively. The Results on boll and locule basis, the significant lowest incidence of pink bollworm was recorded under treatment T2 (2.67 and 2.00%, 20.00 and 13.00%) and it was at par with T6 (2.89 and 2.53%; 21.33 and 14.36%) during 2016 and 2017, respectively.